MA’SUMA AHMEDOVA IJODIDA AYOL RUHIYATI TASVIRI - Ibragimova Zebiniso Yunus qizi, Umida Rasulova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article discusses the depiction of the female psyche in some of the stories of the famous writer Masuma Akhmedova, the artist's skill in depicting the female psychology. In writer's stories, it can be observed that she expresses delicately and impressively the vibrations in a woman's heart, and figuratively describes the tender feelings in her nature. In the stories, the female psyche is shown skillfully by the writer.